New approaches for the asessment and education of children under socio-cultural disadvantages - Majluf, Alegría (2003)
The present paper describes the traditional psychometric parameters thal don 't fit by workingwith children who suffer socio-cultural deprivation (or who are living under socio-cultural disadvantages)and the new assessment and education strategies for this population. Vygotsky's socio-cultural approach, that emphasizes the Zone of Proximal Development, and the Dynamic Assessment and the Mediated Learning developed by Feucrstein and complemented by Coll relatedwith the Significative Learning are stressed.